A new riparian Andean Potamites (Reptilia, Squamata, Gymnophtalmidae) from El Sira Mountains, central Peru, with comments on P. ecpleopus Cope 1875, and on the taxonomy and biogeography of Potamites - Chávez, Germán; Malqui, Jose; Catenazzi, Alessandro (European Journal of Taxonomy, 2021)
We describe a new species of riparian lizard from the foothills and submontane forest of El Sira Communal Reserve, Departamento de Huánuco, Peru, at elevations from 540 to 760 m. We name the new species Potamites hydroimperator sp. nov. because it is the only lizard living in streams in this isolated mountain. The new species is distinguishable from other congeners (except P. ecpleopus) by having longitudinal rows of keeled scales on dorsum, and males with 5–8 lateral ocelli on each flank. Potamites hydroimperator sp. nov. differs from P. ecpleopus by being smaller, having dorsal scales on forelimbs smooth or slightly keeled, subconical tubercles on forelimbs weakly present or absent, and four to five superciliar scales. We comment on variation in the pattern of keeling of dorsal scales among Amazonian lowland, Andean foothills and montane species of Potamites, and the potential relevance of this scalation pattern for taxonomic and biogeographic studies. The new species increases our knowledge of the diverse and endemic herpetofauna of El Sira, and of diversity within the genus Potamites. Despite El Sira’s status as natural protected area, gold mining activities are destroying the streams where we found P. hydroimperator sp. nov., threatening their populations.